The differentiated politicization of free movement of people in the EU. A topic model analysis of press coverage in Austria, Germany, Poland and the UK. Issue 2 (1st February 2023) - Blauberger, Michael; Heindlmaier, Anita; Hofmarcher, Paul; Assmus, Josephine; Mitter, Birgit
ABSTRACT: The free movement of people (FMP) has been a core principle of European Union (EU) integration since its beginnings, but it has recently become contested. This article traces the politicization of FMP, and the topics associated with it, over time and across countries. Rather than constituting a linear or uniform trend, we argue that the politicization of FMP is differentiated: it is driven by particular events such as Eastern enlargement, mitigated by restrictive domestic policies anticipating the expansion of EU free movement rights, and that FMP is salient, but not polarized, from an emigration country perspective. Combining structural topic modelling and qualitative text analysis, we compare three decades of news coverage of FMP in Austria, Germany, Poland and the UK.